If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -7k + 3 = -10 Reorder the terms: 8 + 3 + -7k = -10 Combine like terms: 8 + 3 = 11 11 + -7k = -10 Solving 11 + -7k = -10 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -7k = -10 + -11 Combine like terms: 11 + -11 = 0 0 + -7k = -10 + -11 -7k = -10 + -11 Combine like terms: -10 + -11 = -21 -7k = -21 Divide each side by '-7'. k = 3 Simplifying k = 3
| -1(4x-5)=x | | 2(x-8)+7=5(x+2)-3x-1 | | 4f+g=-2f-14 | | (x^2-2x-8)/(x^3+x^2-2x) | | 2.5y+7.5y=4.2 | | 4f+h=-2g-14 | | B-38=-79 | | x^2+2x-1= | | 7(6x-1)+6(-6x+8)= | | 6[4(2x-1)]=80-8 | | 5(-7+x)=5 | | 2/9*x-4=28 | | 22=p-2+7p | | (12+m)+4= | | 4v+4k+n=s | | 8*x*y= | | 7[5-(-3x-4)]=198x+287 | | 5(2+4n)=-90 | | (17+2x)/(3x+1)=3/4 | | -7a=133 | | 9-3(x-3)-2x=-32 | | 3x+6=2x+x+6 | | x^3y+2y-1=0 | | 480-30x^2=400 | | -2(x+3)+x=0 | | -3x+1=2 | | -3X/15=6 | | 80-3x=5x | | 33+(-6)+4= | | (23/28)x=2 | | 4.9=x-12 | | 5x+4-2x=13 |